Polityka władz wobec społeczności ukraińskiej w latach 1944–1956 - Pisuliński, Jan (Pamięć i Sprawiedliwość, 2004)
The article presents stages of policy of Polish authorities concerning 600–700 000 members of Ukrainian minority inhabiting areas in the South-East Poland. In the discussedperiod that policy was undergoing a large transformation. When communists gained power in Poland they had no elaborated way of behavior. At first it was believed that the problem would solve itself after the agreement with USRR of 9 September 1944 on people exchange. However, vast majority of Ukrainians did not wish to leave their land, thus a compulsory displacement was carried out using the army, often in a brutal way. As not all Ukrainians were deported that time, in spring of 1947 large military force with militia and security service carried out „Vistula action” (Akcja „Wisła”), which officially was to do away with the armed underground of Ukrainian OUN (Organization of Ukrainian Nationalists)-UPA (Ukrainian Insurgent Army) forces. In such a way the rest of Ukrainians (about 150 000) were displaced to farms left by the Germans in northern and western Poland with no right to come back. Thus all the Ukrainian community was made responsible for actions of the underground. Almost 4000 people suspected of collaboration with the underground were placed in the Central Work Camp in Jaworzno, were they were brutallyquestioned.When „Vistula action” was completed, repressions against the Ukrainian community were softened and most of the people put in Jaworzno were set free. However, Ukrainians still had no chance to cultivate their religious and national traditions. Their further displacement into Soviet Ukraine was considered, but these plans were not realized. Actions of the authorities after 1950 shows gradual acceptance of a constant presence of Ukrainiancommunity of 200 000 people and a growing awareness of their needs. Consequently, the policy considering minorities was evolving, so that material situation of the Ukrainians began to improve. Cultivating traditions within the frames of few cultural organizations and teaching in their own language was allowed, although still on the limited scale in totalitarian system. The culmination of this process were changes of 1956. The previousbehavior of the authorities was criticized, issuing an own newspaper and setting up an organization to represent the interests of the minority was allowed. These changes led toequaling the situation of Ukrainian and Polish people. However, the most important postulate of Ukrainian community, that is allowing the majority of Ukrainians displaced within „Vistula action” to come back to their old farms, has not been realized.